2013
DOI: 10.1021/am403534z
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Multifunctional Hetero-Hierarchical Micro/Nanostructure Tetragonal Array with Self-Cleaning, Anticorrosion, and Concentrators for the SERS Detection

Abstract: Heterohierarchical micro/nanostructure tetragonal array consisted of engineering materials of microprotrusion-like Cu and secondary nanostructured dendrite Ag have been fabricated via a primary cell-induced deposition and a facile galvanic displacement reaction combined with photolithography technique on Cu foil. Confined by the circle microwell tetragonal array of the photoresist template, regular microprotrusion-like Cu with the tunable size of diameter can be easily deposited on the surface of Cu foil. Then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…Recently, Zhang et al fabricated hierarchical micro/nanostructure regular array comprising microprotrusion structured Cu covered by nanostructured Ag dendrites via electrochemical reactions combined with photolithography. These fabricated surfaces showed self-cleaning properties across a wide pH range after PFDTS modification (Figure 3d) [62]. …”
Section: Design and Fabrication Of Bio-inspired Extreme Wetting Sumentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Zhang et al fabricated hierarchical micro/nanostructure regular array comprising microprotrusion structured Cu covered by nanostructured Ag dendrites via electrochemical reactions combined with photolithography. These fabricated surfaces showed self-cleaning properties across a wide pH range after PFDTS modification (Figure 3d) [62]. …”
Section: Design and Fabrication Of Bio-inspired Extreme Wetting Sumentioning
confidence: 99%
“…Reproduced from [32,34,61,62,63,64] with the permission by Springer, Copyright 1997 and by ACS Publications, Copyright 2007, 2008, 2013 and by Elsevier, Copyright 2013.…”
Section: Figurementioning
confidence: 99%
“…The superhydrophobic surface with high adhesion has potential applications in many fields, like no loss transfer of microdroplets, biochemical separation, in situ detection, local chemical reactions, and so on. The superhydrophobic surface with low adhesion can be applied to anti‐icing, anti‐bioadhesion, self‐cleaning, and other aspects for a huge applications.…”
Section: Resultsmentioning
confidence: 99%
“…3,6,[19][20][21] There are plenty of hierarchical micro/nanostructure surfaces which have been inspired by nature. [22][23][24][25][26] Jiang et al reviewed the designs of bioinspired multifunctional materials 27 and indicated that biological surfaces have some unique properties e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al reported heterohierarchical micro/nanostructures on Cu foils with a CA of 165 and a sliding angle of less than 2 using photolithography coupled with electrochemical deposition. 3 Although patterned micro/nanostructures have been achieved using this method to obtain superhydrophobicity surfaces, the photomasks used in photolithography are complicated and expensive, 34 limiting their further industrial applications. Femtosecond laser processing is a one-step direct maskless fabrication technique and has intrinsic advantages over traditional methods with respect to controllability and economy.…”
mentioning
confidence: 99%